2012
DOI: 10.1039/c2ee21414h
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and photoelectrochemical investigation of water oxidation with hematite electrodes

Abstract: Atomic layer deposition (ALD) was utilized to deposit uniform thin films of hematite (α-Fe 2 O 3 ) on transparent conductive substrates for photocatalytic water oxidation studies.Comparison of the oxidation of water to the oxidation of a fast redox shuttle allowed for new insight in determining the rate limiting processes of water oxidation at hematite electrodes. It was found that an additional overpotential is needed to initiate water oxidation compared to the fast redox shuttle. A combination of electrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

72
573
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 469 publications
(650 citation statements)
references
References 69 publications
72
573
2
3
Order By: Relevance
“…Our transient kinetic studies also suggest that the lifetime required for water oxidation by hematite photoholes is on the order of 1 s, a conclusion supported by recent frequency domain photoelectrochemical analyses (18,32,41). In particular, we observe here a close correlation between the bias dependence of the appearance of the long-lived photohole transient signal and the bias requirement for the observation of anodic photocurrents, providing further confirmation of requirement of longlived holes to enable water oxidation.…”
Section: Discussionsupporting
confidence: 69%
“…Our transient kinetic studies also suggest that the lifetime required for water oxidation by hematite photoholes is on the order of 1 s, a conclusion supported by recent frequency domain photoelectrochemical analyses (18,32,41). In particular, we observe here a close correlation between the bias dependence of the appearance of the long-lived photohole transient signal and the bias requirement for the observation of anodic photocurrents, providing further confirmation of requirement of longlived holes to enable water oxidation.…”
Section: Discussionsupporting
confidence: 69%
“…39 Films were prepared by 1,000 ALD cycles and measured to be ~55 nm by absorption measurements (Perkin Elmer, Lambda 35 with a Labsphere integrating sphere) corrected for reflection as described previously, as well as ellipsometric measurements (Horiba Jobin Yvon, Smart-SE). 36 Films were characterized by Raman Spectroscopy and XRD of these films previously. 36 Hematite electrodes were masked with a 60 m Surlyn film (Solaronix) with a 0.28 cm 2 hole to define the active area and to prevent scratching of the thin films.…”
Section: Methodsmentioning
confidence: 99%
“…The thin film hematite was prepared by atomic layer deposition (ALD), [34][35][36] and were subsequently coated with Co-Pi films by photoelectrodeposition. These thin hematite films have been shown to be a good model system for studying the limitations of water oxidation at the hematite surface.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that these surface traps are FeO intermediates and the formation of these species by proton-coupled oxidation of surface hydroxide species constitutes the first step of water oxidation on hematite electrodes. 16,25 In other materials, like GaN for instance, 26 surface traps are mainly due to the morphology of the material and are present in the dark and under illumination. Consequently, in the latter situation, the voltammetry plots display a comparable capacitive peak for both pretreatments.…”
Section: Irect Transformation Of Solar Energy Into Chemical Energymentioning
confidence: 99%